Pelatihan Canva sebagai Media Penguatan Literasi Digital bagi Siswa MA Nurul Wahid Al Wahyuni Sumberan Besuk - Eka Diana; Uswatun Hasanah; Riska Purnama Sari; Unzila Khumairohtus Shiyamah (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service programme aims to improve the digital literacy of Madrasah Aliyah Nurul Wahid Al Wahyuni Sumberan Besuk students through training on the use of Canva as a graphic design medium. Based on initial analysis, students have low digital literacy skills, while the adoption of technology in learning is still limited. This training involves the introduction of digital literacy, Canva interface, to the creation of graphic design based on academic and non-academic needs. The training process includes observation, module development, interactive session implementation, and evaluation of student work. With a practical approach and hands-on guidance, students were introduced to graphic design skills, such as creating posters and infographics, as well as an understanding of digital ethics. The results of the programme showed an increase in students' skills in utilising Canva to support learning. This programme not only provides a direct impact in the form of improved technical competencies, but also contributes to the development of broader digital literacy skills to face the challenges of the digital era.